Flunitrazepam induces geometrical changes at the lipid-water interface - Garcia, Daniel Asmed (2001)
Flunitrazepam (FNTZ) effects on molecular packing and surface curvature in artificial model membranes were investigated. FNTZ, from the subphase under dipalmitoylphosphatidylcholine (dpPC) monolayers at the air-water interface, expanded the surface pressure-area isotherm and induced an increment in the limiting area; in this conditions, the collapse pressure of dpPC decreased, indicating a lowering in the stability of the monolayer. Thermodynamic-geometric correlations based on molecular parameters predicted a decrement in the aggregation number and stability, and an increase in the curvature of the self-aggregated structure of dpPC in aqueous medium in the presence of FNTZ. Accordingly, negative-staining electron microscopy of dpPC aqueous dispersions showed that the mean diameter of dpPC vesicles decreased 2 and 2.87 times in the presence of 10 nM and 50 μM FNTZ, respectively, compared with control samples. The release of a soluble marker entrapped in dpPC liposomes increased slightly respect to the control in the presence of FNTZ. In dpPC-dpPE mixed liposomes 50 μM FNTZ induced a decrement in the amount of the aminophospholipid exposed to the outer monolayer. Concluding, an FNTZ-induced expansion of dpPC-water interface region affected the constraints imposed on the lipid-water system by the molecular geometry, interacting free energies and entropy that determine the shape of a multimolecular structure. In liposomes composed of a pure phospholipid, the bilayer expansion leaded, through a structure instability, to reduce the liposome size; in mixed liposomes, phospholipid molecules translocation could be observed as another compensating mechanism of the initial perturbation. These results may be relevant for understanding benzodiazepines' effects non-mediated by membrane receptors. (C) 2001 Elsevier Science B.V.